An Analysis on Special Education: Teachers Role and Responsibilities: Challenges and Prospects in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Education is one of the most effective tools which Children withSpecial Needs could achieve the social and economic empowerment. Educationholds much importance for Children with Special needs as they have been asubject of discrimination for a long period of time. A special educationteacher often has students with varying learning, mental, physical andemotional disabilities. Teachers whose students have mild to moderatedisabilities may work with the children in a regular classroom alongside theclassroom teacher. In other situations, the special education teacher may haveher own classroom. Some special education teachers teach lessons similar tothose of regular education students, while other special education teachers teachstudents independent living skills. However it gives them a holisticperspective with respect to dealing with diversity or challenge negativeattitudes. The challenges and prospects in India are elucidated in the presentpaper.